Detection of genomic loci associated with chromosomal recombination using high-density linkage mapping in Setaria. Issue 1 (December 2017) - Jia, Guanqing; Wang, Haigang; Tang, Sha; Zhi, Hui; Liu, Sichen; Wen, Qifen; Qiao, Zhijun; Diao, Xianmin
Abstract Meiotic recombination is essential to sexual reproduction and the generation of genetic diversity. Variation in recombination rates is presently of particular interest due to efforts being made to increase the rate of genetic gain in agricultural crops by breaking up large linkage disequilibrium blocks containing both beneficial and detrimental alleles. Here, a high-density genetic linkage map of Setaria was constructed using tunable genotyping by sequencing (tGBS) analysis of a population of recombinant inbred lines (RILs). Several regions of the Setaria genome exhibited significant levels of segregation distortion (SD), and recombination crossovers (COs) were also detected. The regions with high SD generally tended to have fewer COs, particularly for pericentromeric chromosomal areas. Recombination crossovers detected in Setaria were unevenly distributed across the genome and occurred more often in intergenic regions. Quantitative trait loci (QTLs) contributing towards the recombination frequency (Type I) and occurrence of COs in designated loci (Type II) were identified, and Type II QTLs garnered higher statistical power. The result of this study suggest that QTLs analysis of Type II traits using RILs might provide an opportunity to further understand meiotic recombination using high throughput genome sequencing and genotyping technologies.